Predictive maintenance for rotating machinery by using vibration analysis - N., Jamil; M. F., Hassan; S. K., Lim; A. R., Yusoff (Faculty Mechanical Engineering, UMP, 2021)
This paper presents a complete and well tested virtual instrument (VI) for computer numerical control (CNC) machine predictive maintenance. The national instrument (NI) hardware, LabVIEW software and accelerometer sensor are acquired for the vibration analysis integrated with virtual instrument were developed based on the vibration severity chart threshold in ISO 10816. Validation experiments of the predictive maintenance module were utilized on drilling and milling processes to test and verify the effectiveness of the module. Results obtained from current module can monitor and provide the machine conditions at different condition of good, satisfactory, unsatisfactory, and unacceptable for rotating machinery status according to the vibration severity chart as per ISO 10816.